A Needs-led Framework for Understanding the Impact of Caring for a Family Member With Dementia. (9th October 2017) - Pini, Simon; Ingleson, Emma; Megson, Molly; Clare, Linda; Wright, Penny; Oyebode, Jan R
Abstract: Background and Objectives: Approximately half the care for people with dementia is provided by families. It is therefore imperative that research informs ways of maintaining such care. In this study, we propose that a needs-led approach can provide a useful, novel means of conceptualizing the impact of caring on the lives of family carers. Our aim was to develop and present a needs-led framework for understanding how providing care impacts on carers' fulfilment of needs. Design and Methods: In this qualitative study, we conducted 42 semistructured interviews with a purposively diverse sample of family carers to generate nuanced contextualized accounts of how caring impacted on carers' lives. Our inductive thematic analysis focused upon asking: "What need is being impacted here?" in order to generate a needs-led framework for understanding. Results: Nine themes were widely endorsed. Each completed the sentence: "Being a carer impacts on fulfilling my need to/for….": Freedom; feel close to my relative; feel in control of my life; be my own person; protect my relative; share/express my thoughts and feelings; take care of myself; feel connected to the people around me; get things done. Discussion and Implications: These needs echo those from other research areas, with relational needs emerging as particularly central. The needs-led approach offers a perspective that is able to capture both stresses and positive aspects of caregiving. We recommend that clinical interviewing using Socratic questioning to discover human needs that are being impacted by caring would provide a valuable starting point for care planning.